Microstructural Effects of Mn2+ ions in ZnO Nanoparticles. Issue 9 (29th August 2013) - Rajeswari, P.; Dhanuskodi, S.
<x xml:space="preserve">Abstract</x> Semiconducting ZnO nanoparticles with manganese content 0 at. %, 5 at. % and 10 at. % were prepared by co‐precipitation technique and XRD reveals that the average crystallite size D is 10.2 nm, 7.62 nm and 7.06 nm respectively. The individual contributions of the size and strain to the XRD peak broadening were investigated by Williamson‐Hall (W‐H) analysis. The strain, stress and energy density were calculated more precisely by uniform deformation model (UDM), uniform stress deformation model (USDM), uniform deformation energy density model (UDEDM) and size‐strain plot (SSP) method. The average particle size from HRTEM analysis is 13 ± 2 nm. The evaluated average crystallite size… <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>